산림치유프로그램이 소방공무원의 외상 후 스트레스 및 기분상태 변화에 미치는 효과 - 박충희(Choong-Hee Park); 강재우(Jaewoo Kang); 안미영(Miyoung An); 박수진(SuJin Park) (한국화재소방학회 논문지, 2019)
This study was conducted to investigate the effects of a forest therapy program on post-traumatic stress disorder (PTSD) and mood states of fire fighters. A total of 293 participants completed two psychological questionnaires before and after the program was conducted: the Post Traumatic Stress Disorder Checklist (PCL) and the Profile of Mood States (POMS). Data were analyzed with paired t-test and ANCOVA using SPSS 24.0. The PTSD results showed a significant decrease from 11.38 ± 12.58 points before the program to 6.91 ± 10.50 points after the program. Results of the POMS questionnaire revealed an increase in positive factors and a decrease in negative factors, with a significant overall decrease in POMS results from 8.58 ± 18.47 points before the program to -0.63 ± 15.83 points after the program. As a result of analyzing the differences in stress reduction effects according to the amount of sleep participants had, PTSD showed improvement at 6-8 hours of sleep. These results are expected to be utilized as a basis for stress management and relief in fire fighters. 본 연구는 국립산림치유원에서 실시한 4박 5일형 산림치유프로그램이 소방공무원의 외상 후 스트레스 및 기분상태 변화에 미치는 효과를 알아보고자 수행되었다. 소방공무원 293명을 대상으로 설문조사를 실시하였으며, SPSS 24.0을 활용하여 빈도분석, 대응 t-검정 및 공분산분석을 실시하였다. 산림치유프로그램 참여 전과 후의 외상 후 스트레스, 기분상태의 차이 및 인구학적 특성에 따른 차이를 분석하였다. 외상 후 스트레스 결과, 참여 전 평균 11.38 ± 12.58점에서 참여 후 6.91 ± 10.50점으로 감소하여 통계적으로 유의한 영향을 미치는 것으로 나타났다. 기분상태검사 결과, 긍정적 요인은 증가하였고, 부정적 요인은 감소하였다. 전체 기분상태 또한 프로그램 참여 전 8.58 ± 18.47점에서 참여 후 -0.63 ± 15.83점으로 통계적으로 유의한 영향을 미치는 것으로 나타났다. 수면시간에 따른 스트레스 저감 효과 차이 분석 결과, 외상 후 스트레스는 수면시간이 6~8시간일 때 효과가 높게 나타났다. 본 연구결과는 소방공무원의 외상 후 스트레스 관리와 해소를 위한 방법이 될 수 있는 근거자료로 활용되기를 기대한다.